PENGEMBANGAN MEDIA MONOPOLI BERBASIS CERITA RAKYAT JAWA UNTUK MENINGKATKAN KETERAMPILAN MEMBACA DAN MENULIS AKSARA JAWA KELAS IV SEKOLAH DASAR - Rizka Istianah; Novi Setyasto (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
Javanese language as one of the local content will run effectively if supported by innovative learning media and can attract students' attention. Based on the results of pre-research data at SDN 01 Pucakwangi, it has been found that the problem of using learning media has not attracted students' attention and the media seems monotonous only using books and pictures. This problem results in many students not having the skills to read and write Javanese characters so that from student learning outcomes there are still many students who have not reached the KKM. This study aims to develop, test the feasibility, and effectiveness of Javanese folklore-based mnopoli learning media to improve reading and writing skills of Javanese script in Javanese learning content of Javanese script material in class IV SDN 01 Pucakwangi. This study uses the type of research and development with the Borg and Gall development model. The results of this study indicate that Javanese folklore-based monopoly media is very feasible with a percentage value from material experts of 100% and a percentage of media experts of 95%. This learning media is effective in reading and writing Javanese script skills based on the t-test. The t-test conducted on both skills obtained the same results, namely sig. (2-tailed) of 0.000 <0.05. The results of student responses obtained a percentage of 93.5%. Then based on the results of the N-gain test on Javanese reading skills, namely 0.51 and writing skills of 0.54 in the medium category. The conclusion of this study is that Javanese folklore-based monopoly media is feasible and effective to use to improve reading and writing skills of Javanese characters.